Direct solar FTIR measurements of CO2 and HCl in the plume of Popocatépetl Volcano, Mexico - Stremme, Wolfgang; Grutter, Michel; Baylón, Jorge; Taquet, Noemie; Bezanilla, Alejandro; Plaza-Medina, Eddy; Schiavo, Benedetto; Rivera, Claudia; Blumenstock, Thomas; Hase, Frank (Frontiers in Earth Science, 2023)
Volcanic CO 2 emissions inventories have a great importance to understand the geological carbon cycle. Volcanoes provide the primary pathway for Solid Earth volatiles to reach the Earth's atmosphere and have the potential to significantly contribute to the carbon-climate feedback.2012-2016 could be determined from a statistical treatment of the detected CO 2 and HCl columns in the IR spectra, and their corresponding molecular ratios. A total of 25 events were used to derive a mean CO 2 /HCl molecule ratio of 11.4± 4.4 and an average HCl emission rate of (3.0±0.3) kg/s could be determined. The CO 2 emissions of Popocat épetl were found to be around 0.32% of the total anthropogenic CO 2 emissions in the country (Instituto Nacional de Ecología y Cambio Clim ático (INECC), 2018) and 3.6% of the Mexico City Metropolitan Area (MCMA) , according to the corresponding emission inventories (Espinoza et al., 2018). CO 2 emissions from the Popocat épetl volcano can be considered to play a negligible role for the global CO 2 budget, but should be taken into account for the study of the carbon cycle on regional scales.